Development of pH-sensitive self-nanoemulsifying drug delivery systems for acid-labile lipophilic drugs. (March 2016) - Zhao, Tianjing; Maniglio, Devid; Chen, Jie; Chen, Bin; Migliaresi, Claudio
Graphical abstract: Highlights: We propose an innovative approach for preventing the degradation in stomach and improving the solubilization and dissolution rate of acid-labile lipophilic bioactive compounds. The developed SNEDDS formulations are pH-sensitive, with self-emulsification occurring in the intestine. In vitro release profile from pH-SNEDDS is much higher if compared with that from powder and commercial tablets product. This is the first time that such a study on the combination of controlled stimulus with self-emulsification technique. Abstract: Oral administration is the most convenient way of all the drug delivery routes. Orally administered bioactive compounds must resist the harsh acidic fluids or enzyme digestion in stomach, to reach their absorbed destination in small intestine. This is the case for silibinin, a drug used to protect liver cells against toxins that has also been demonstrated in vitro to possess anti-cancer effects. However, as many other drugs, silibinin can degrade in the stomach due to the action of the gastric fluid. The use of pH-sensitive self-nanoemulsifying drug delivery systems (pH-SNEDDS) could overcome the drawback due to degradation of the drug in the stomach while enhancing its solubility and dissolution rate. In this paper we have investigated pH-sensitive self-nanoemulsifying formulations containing silibinin as model drug. Pseudo-ternary phase diagrams have been constructed in order to identify the self-emulsification regions under different pH. Solubility of silibinin in selected formulations has been assessed and stability of the pure drug and of the silibinin loaded pH-SNEDDS formulations in simulated gastric fluid had been compared. Droplet size of the optimized pH-SNEDDS has been correlated to pH, volume of dilution medium and silibinin loading amount. TEM (transmission electron microscopy) studies have shown that emulsion droplets had spherical shape and narrow size distribution. In vitro drug release studies of the optimal pH-SNEDDS indicated substantial increase of the drug release and release rate in comparison to pure silibinin and to the commercial silibinin tablet. The results indicated that pH-SNEDDS have potential to improve the biopharmaceutics properties of acid-labile lipophilic drugs.